Improving Learning Quality Through Infrastructure Management - Mutiara, Yeni; Arafat, Yasir; Furkan, Nuril (Graduate Program Magister Manajemen Pendidikan, 2022)
The purpose of this research is to analyze and explain the design, organization, execution, and oversight of infrastructure facilities in order to improve the quality of learning at SMP Negeri 01 Belitang II. This study employs a qualitative approach. Data analysis employs analysis, namely data reduction, data display, and conclusion making. The study's findings were examined through four components of infrastructure management implementation: planning, organizing, implementing, and supervising in order to improve the quality of learning at SMP Negeri 01 Belitang II. The infrastructure design step involves developing many programs and carefully preparing so that students may have pleasant amenities while not incurring high school costs. The organizational stage begins with the selection of those who will carry out the responsibilities or job of task division, including the principal, vice principal, teachers, and TU personnel. The principal determines the procedure of implementing infrastructure with the cooperation of the treasurer, and the deputy head of the facility supplies any items as needed. The infrastructure facilities are then supervised to ensure that their usage and maintenance function smoothly and do not interfere with the continuous learning process.